2007
DOI: 10.1185/030079907x187874
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study to determine the MTD of paclitaxel given three times per week during concurrent radiation therapy for stage III non-small cell lung cancer

Abstract: 15 mg/m2 of paclitaxel, three times a week, concurrently with 3D-conformal radiotherapy for patients with locally advanced NSCLC after 2 or 3 cycles of induction chemotherapy is a safe and effective dose, according to our preliminary study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Enrolled patients were randomly assigned to one of the two treatment arms using the published maximum tolerated dose (18). CCRT was initiated 4–8 weeks after completion of induction chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enrolled patients were randomly assigned to one of the two treatment arms using the published maximum tolerated dose (18). CCRT was initiated 4–8 weeks after completion of induction chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…This clinical trial has reported promising tumor response rates and a high rate of infield tumor control with low toxicities (1517). We also conducted a phase 1 clinical study testing this hypothesis-based study design in China (18). Following up the phase 1 study, we conducted a multicenter randomized phase 3 study comparing two low-dose sensitizing paclitaxel schedules of CCRT for LA-NSCLC.…”
Section: Introductionmentioning
confidence: 99%